Impact of Microbial Enzymes on Growth Performance, Micronutrient Digestibility, Tissue Protein Contents and Endogenous Enzyme Activities of Broiler Chickens Fed on Vegetable Protein Diets - Hossain, M.A.; Islam, A.F.; Iji , P.A. (International Journal of Poultry Science, 2014)
A study was conducted to investigate the effects of dietary protein sources and microbial enzyme supplementation on amino acid and mineral digestibility, tissue protein contents and endogenous enzyme activities of broiler chickens. Ross 308 day-old male broiler chicks (n = 160) were assigned randomly to four dietary treatments, each replicated five times, eight chicks per replicate, in a 2 x 2 factorial design. Two basal diets were formulated with soybean (SBM) and canola (CM) meals at a ratio of 75:25, respectively, along with basal grains and fed to the birds as such or supplemented with enzymes from 1 to 35 days. Enzymes had a positive effect on the gross responses (feed intake, body weight and feed conversion ratio) of the broiler chickens at 35 days. However, feed intake was significantly different (p0.05) body weight and feed conversion ratio (FCR) between 1 and 35 days. Tissue protein contents and endogenous enzyme activities at 21 days (except for maltase) were unaffected by dietary sources and microbial enzyme supplementation. The activity of maltase was higher (p